2021
DOI: 10.1111/jasp.12785
|View full text |Cite
|
Sign up to set email alerts
|

The intergroup sensitivity effect in mergers and acquisitions: Testing the role of merger motives

Abstract: Research has shown that people are more defensive to criticism when it stems from an outgroup member, compared to an ingroup member (the intergroup sensitivity effect: ISE). We conducted two online vignette experiments to examine the ISE in the context of an organizational merger and the role of merger motives for the ISE. We predicted that the ISE would also emerge in mergers and acquisitions (M&As), but people would respond less negatively to criticism from the outgroup when the motive for the merger is desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…These findings also extend the insights of previous studies from the social identity approach such as Liang et al (2021), who highlight how the ingroup sensitivity effect is relevant for M&As demonstrating that acquirer employees might respond negatively to the criticisms of acquired employees even when learning is the motive of the acquisition. Therefore, acquirer managers can implement actions to facilitate the emergence of serendipitous value and transfer of capabilities (Graebner, 2004; Colman, 2020).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings also extend the insights of previous studies from the social identity approach such as Liang et al (2021), who highlight how the ingroup sensitivity effect is relevant for M&As demonstrating that acquirer employees might respond negatively to the criticisms of acquired employees even when learning is the motive of the acquisition. Therefore, acquirer managers can implement actions to facilitate the emergence of serendipitous value and transfer of capabilities (Graebner, 2004; Colman, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, these identity dynamics are under-investigated in the context of the acquisition of capabilities. Liang et al (2021) conducted two experiments arguing that people would respond less negatively to criticisms of outgroup members when the motive is access to their valuable knowledge. While their hypothesis is not confirmed, they call for more research on intergroup dynamics with specific attention to merger motives.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Our findings have implications for leadership and management practice. Acquiring and acquired organizations need to approach the post-merger integration with a growth mindset (Murphy & Dweck, 2010), learn from the outgroup members by integrating feedback as legitimate and constructive (Liang et al, 2021). The AOI is an important factor to such a constructive ingroup and outgroup collaboration and it helps avoid resistance resulting from pre-merger group membership.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that mediamessages should aim to reduce threat and make sure to convey their benevolent intention, as should those who participate in public debate (Adelman & Verkuyten, 2020). In line with this claim, recent research observed a reduced ISE in an organizational setting when the outgroup expressed benevolent intentions (Liang et al, 2021). In addition, more specific COVID-related emotions, such as fear, rage, sadness, or boredom, may play a more prominent role (e.g., Carstensen et al, 2020;Wolff et al, 2020).…”
Section: Discussionmentioning
confidence: 91%